Blood Pressure and Kidney Function in Preeclampsia: a Scoping Review - Mandias, Reagen Jimmy; Shintya, Lea Andy (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
Preeclampsia is a serious pregnancy complication characterized by hypertension and impaired renal function. Understanding the relationship between maternal blood pressure and kidney function is essential for effective management to reduce adverse maternal and neonatal outcomes. This scoping review aimed to map the current evidence on the interaction between blood pressure and renal function in preeclampsia, including studied variables, methodologies, and research gaps. The review followed the Arksey and O’Malley framework and PRISMA-ScR guidelines, with a comprehensive search of MEDLINE, CINAHL, ERIC, and ScienceDirect databases. A total of 23 studies met the inclusion criteria, with most conducted in Asia, particularly China, and Latin America, especially Brazil. Seven major variable categories were identified: blood pressure, renal function, early pregnancy biomarkers, circulating biomarkers, inflammatory markers, molecular markers, and postpartum outcomes. The findings indicate a strong association between hypertension and renal dysfunction driven by placental insufficiency, angiogenic imbalance, and immune activation. Approximately 20.3% of women experienced persistent hypertension and 33.1% had ongoing proteinuria up to six months postpartum. In conclusion, preeclampsia involves complex pathophysiological mechanisms with potential long-term effects, highlighting the need for further research to elucidate molecular pathways and develop preventive strategies. Preeklampsia merupakan komplikasi kehamilan serius yang ditandai oleh hipertensi dan gangguan fungsi ginjal. Pemahaman hubungan keduanya penting untuk pengelolaan yang efektif guna menurunkan risiko pada ibu dan bayi. Tinjauan cakupan ini bertujuan memetakan penelitian terkait interaksi tekanan darah dan fungsi ginjal pada preeklampsia, termasuk variabel, metode, dan kesenjangan penelitian. Studi dilakukan menggunakan kerangka Arksey dan O’Malley serta pedoman PRISMA-ScR, dengan pencarian pada basis data MEDLINE, CINAHL, ERIC, dan ScienceDirect. Sebanyak 23 studi memenuhi kriteria, mayoritas berasal dari Asia (terutama Tiongkok) dan Amerika Latin (Brasil). Tujuh kelompok variabel diidentifikasi, meliputi tekanan darah, fungsi ginjal, biomarker kehamilan dini, biomarker sirkulasi, penanda inflamasi, penanda molekuler, dan luaran pascapersalinan. Hasil menunjukkan hubungan erat antara hipertensi dan gangguan ginjal yang dipengaruhi insufisiensi plasenta, disregulasi angiogenesis, dan aktivasi imun. Sekitar 20,3% wanita mengalami hipertensi persisten dan 33,1% proteinuria hingga enam bulan pascapersalinan. Disimpulkan bahwa preeklampsia melibatkan mekanisme kompleks dengan dampak jangka panjang, sehingga diperlukan penelitian lanjutan untuk memahami mekanisme molekuler dan mengembangkan strategi pencegahan.